Global financial markets and the risk premium on U.S. equity - Chan, K.C.; Karolyi, G.Andrew; Stulz, RenéM. (Journal of Financial Economics, 1992)
There is a significant foreign influence on the risk premium for U.S. assets. Using a bivariate GARCH-in-mean process, we find that the conditional expected excess return on U.S. stocks is positively related to the conditional covariance of the return of these stocks with the return on a foreign index but is not related to its own conditional variance. Further, we are unable to reject the international version of the CAPM. We present evidence for different model specifications, multiple-day returns, and alternative proxies for foreign stock returns.